Nonadditivity and anisotropy of the polarizability of clusters: relativistic finite-field calculations for the Xe dimer - Bezchastnov, Victor G.; Pernpointner, Markus; Schmelcher, Peter; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2010)
We present all-electron relativistic studies of the polarizability properties of the Xe dimer. The studies rely on finite-field calculations of the dimer energies obtained by ab initio methods including electron correlations. An extended set of basis functions is designed in order to ensure a high accuracy of the calculations. Particular attention is paid to the analysis of the nonadditivity and anisotropy of the polarizability of the dimer. It is found that the polarizability of the dimer relative to that of the atoms can be accurately described analytically, at least for internuclear distances around and larger than the equilibrium distance of the dimer.
Gesehen am 31.01.2023